Working toward durable Solutions to internal displacement: Recommendations of the UN High-Level Panel on Internal Displacement - Nadine Knapp; Anne Koch (Stiftung Wissenschaft und Politik (SWP), 2021)
In September, the United Nations (UN) Secretary-General's High-Level Panel on Internal Displacement issued its final report. In it, the Panel called for a shift in emphasis from short-term humanitarian to longer-term development-oriented approaches and thus a focus on durable solutions. The Panel's key reform proposals - particularly the establishment of a Global Fund and the appointment of a UN Special Representative on the issue - are unlikely to receive widespread support at the international level at this point. Nevertheless, the report offers important starting points for addressing protracted internal displacement including: first, new incentive structures and accountability mechanisms to encourage the active participation of directly affected governments; and second, the operationalisation of the Humanitarian-Development-Peace Nexus (HDP Nexus). In order to breathe life into these recommendations, the new German government should adopt an inter-agency approach to engage in the follow-up process of the High-Level Panel.
Keywords: 320